Advanced construction of heterostructured InCrO4–TiO2 and its dual properties of greater UV-photocatalytic and antibacterial activity. Issue 94 (14th October 2015) - Kamalakkannan, J.; Chandraboss, V. L.; Prabha, S.; Senthilvelan, S.
<x xml:space="preserve">Abstract</x> Advanced recylable heterostructured InCrO4–TiO2 was prepared by a simple co-precipitation method, and exhibits high UV-photocatalytic activity and antibacterial activity mechanism owing to the behaviour of its electrons and holes.